Persepsi Petani dalam Penerapan Elisitor Biosaka di Kecamatan Kebakkramat Kabupaten Karanganyar - Arifuddin, Muhammad Fikri (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2024)
Biosaka is a formula for agriculture that comes from plant extraction (all biodiversity). Farmers' understanding and assessment of implementing biosaka depends on the perception of each farmer. The aim of this research is to describe the factors that shape farmers' perceptions and farmers' perceptions in implementing biosaka elicitors in Kebakkramat District, Karanganyar Regency; analyzed the influence of non-formal education variables, land ownership status, farmer involvement in farmer groups, the role of agricultural instructors, the benefits of biosaka on farmers' perceptions in implementing biosaka elicitors in Kebakkramat District, Karanganyar Regency. This research method is a quantitative method. The research location is Kebakkramat District, Karanganyar Regency. A sample of 47 respondents used the Slovin formula. Data analysis methods are divided into instrument tests, classical assumption tests, ordinal to interval (MSI) data transformation, multiple linear regression data analysis, and hypothesis testing. The research results show (1) farmers' perceptions of the application of biosaka are classified as good in terms of understanding and assessment; (2) partially the variables of non-formal education, the role of agricultural instructors, and the benefits of biosaka have a significant effect on farmers' perceptions, while land ownership status and farmer involvement in farmer groups do not have a significant effect on farmers' perceptions. Simultaneously, perception-forming factors have a significant influence on farmers' perceptions.